(untitled) (Bioresearch Communications, 2022)
This study aimed to screen the phytochemical profile, antioxidant activity, and antibacterial activity of a 70% methanolic extract of Rosenvingea sp., which was collected from Bay of Bengal, Bangladesh. A total of five phytochemicals were detected in the Rosenvingea methanolic extract, including steroids, glycosides, flavonoids, alkaloids, and tannins. The 2,2-diphenyl-1-picrylhydrazyl (DPPH) scavenging experiment exhibited antioxidant activity though it is a weak antioxidant than standard ascorbic acid. The 70% methanol extract had an LC50 of 13.26 mg/mL in the Artemia lethality bioassay, whereas the positive control (K2Cr2O7) had an LC50 of 59.97 μg/mL, indicating the non-toxicity in both Mayer’s and Clarkson’s indexes. The agar disc diffusion method was used to investigate the antibacterial activity of a methanol extract of Rosenvingea sp. against Gram-positive and Gram-negative bacteria species (Staphylococcus aureus, Bacillus cereus, Pseudomonas aeruginosa, Salmonella, and Klebsiella pneumonia) which showed strong antibacterial activity mostly against Staphylococcus aureus, Pseudomonas aeruginosa, Klebsiella pneumonia, and Salmonella with zones of inhibition of 6.66±1.15mm, 5.66±0.57mm, 5.33±0.57 mm & 3.33±0.57 mm respectively. This study found Rosenvingea sp. from the Bay of Bengal to be a promising source of phytochemical, antioxidant, and antibacterial properties. However, further research is needed to establish its economic potential in the food and pharmaceutical industries. Bioresearch Commu. 9(1): 1252-1262, 2023 (January)